Conservation Study of the Argan Oil by Thermogravimetry - Fdili Alaoui, B.; Zeriouh, A.; Belkbir, L. (Asian Journal of Chemistry, 2010)
The arganier, typically Moroccan wood, offers innumerable services: excellent wood and coal for heating, real grazing by its foliage, excellent fodder by the pulp of fruit and source of oil by the seeds. The argan oil, to edible or cosmetic use and owing to its wealth in essential fatty acids (linoleic acid (33.15%) and oleic acid (46.65%)), is able to reduce the rate of blood cholesterol and to warning the atherosclerosis. Our work is a contribution to the determination of the characteristics of this particular oil. The studies showed that the oil preserves relatively well by resisting several months to the oxygen owing to the presence of polyphenols and tocopherols. It becomes degradable easily when it is carried to 64°C for several days.